Factors affecting T2DM patients' behaviors associated with integrated treatment and prevention services in China - Ran Zhao; Xia Zhang; Sizhe Wang; Nan Zhao; Dianjiang Li; Hong Fan (BMC, 2023)
Abstract Objective To explore the relationship between type 2 diabetes mellitus (T2DM) patients' attitude, subjective norms (SN), perceived behavioral control (PBC), behavioral intention (BI) and behavior associated with integrated treatment and preventive (ITP) services. Methods A convenient sampling method was employed at a community health center in Nanjing, China between January and July 2022. The collected data were processed using Epidata 3.1, SPSS 26.0, and AMOS 24.0. Descriptive statistics and a structural equation model based on the theory of planned behavior (TPB) were used to explore the correlation between the study variables. Results 430 participants were eventually included, with a response rate of 98.6%. The mean age was 72.50 ± 5.69 years. The TPB model proved to be suitable and explained 41% of the variance in the BI. Attitude (β = 0.289, P < 0.001), SN (β = 0.314, P < 0.001) and PBC (β = 0.261, P < 0.001) were the main predictors of BI, and the SN was the strongest. BI (β = 0.452, P < 0.001) and PBC (β = 0.452, P < 0.001) had similar direct effects on patients' behavior. Conclusion The TPB model explained the behavioral variations associated with ITP services and provided a framework for developing targeted interventions and improving community-based ITP services for T2DM. To encourage patients to engage in desirable behaviors, interventions should focus on modifying patients' SN towards behavior associated with ITP services by promoting peer pressure and increasing the family's emphasis on health.